PHYSICAL EDUCATION OF SECONDARY SCHOOL STUDENTS USING ULTIMATE FRISBEE - Rymar, Olha; Sorokolit, Nataliia; Romanchuk, Olha; Yaroshyk, Marta; Solovey, Alla; Khanikiants, Olena; Malanchuk, Halyna; Shevtsiv, Uliana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The article theoretically substantiates, develops, experimentally verifies the effectiveness of Ultimate Frisbee authors’ training program for secondary school students to improve fitness level. There was positive dynamics in fitness level in the experimental group. The research aim is to determine the effectiveness of Ultimate Frisbee equipment use in physical education of secondary school students. The fitness level has been determined and the effectiveness of the Ultimate Frisbee program in physical education of secondary school students was verified. 45 schoolchildren were engaged into the study. Research methods: literary sources analysis; methods of obtaining empirical data (determining fitness level by T. Krutsevich methods); pedagogical experiment; mathematical statistics methods. The program to introduce Ultimate Frisbee into the physical education lessons for secondary school students has been presented and scientifically substantiated. The content of the program included studying the history of the game, the basics of game technique and tactics, how to play Ultimate Frisbee, refereeing rules; development of competitive activity skills; increasing fitness level. The developed program has been implemented into the educational process and its effectiveness has been proven. The results of the study showed the positive effect on secondary school students fitness level, which was confirmed by the mathematical statistics methods.